“ICAOEnglish” Educational Website Prototype Based on Figma for ICAO English Language Proficiency Test Learning - Ershanda Ardini Putri; Yohanes Hariadi Prasetya; Ahmad Bahrawi; Lusiana Dewi Kusumayati; Meita Maharani Sukma; Dimas Arya Soeadyfa Fridyatama; Taciana Lavinea Braz Naisia (Politeknik Penerbangan Surabaya, 2026)
This study aims to Design a prototype of an educational website called “ICAOEnglish,” developed using Figma as a Learning media for the ICAO English Language Proficiency Test. The research employed a Research and Development (R&D) method using the ADDIE Development model (Analysis, Design, Development, Implementation, and Evaluation). The instruments used included a needs Analysis questionnaire, a translational validation sheet by experts, and structured interviews with prospective users. The final product of this study is an educational website prototype named “ICAOEnglish,” which contains materials based on the elements of the ICAO English Language Proficiency test. The results show that the developed website prototype meets user needs based on the needs Analysis, is validated by experts in terms of both content and technical aspects and received positive responses from prospective users after prototype testing. This study is expected to serve as a foundation for further Development of technology-based learning media in aviation education.